Socio-Ecological Impact of Unauthorized Gold Mining in West Dumoga, Bolaang Mongondow - Mokoagow, Tania Fahlensia (Universitas Gorontalo, 2019)
Unlicensed Gold Mining (Penambangan Emas Tanpa Izin ? PETI) is a mining business undertaken by an individual, or a group of people, or a legal entity incorporated in its operation without licenses and government agencies in accordance with applicable laws and regulations. PETI activities that do not follow the correct mining rules, have resulted in environmental damage, waste of mineral resources, and mine accidents. Besides that, PETI not only causes the potential revenue to decrease, but also the state/government must spend enormous funds to repair environmental damage.This research takes place in West Dumoga, Bolaang Mongondow District, North Sulawesi Province which has several points which become the location of unlicensed gold mining (PETI). The purpose of this study is to determine the impact of environmental damage caused by gold mining. Besides, this research will trace the socio-economic impact caused that harm the surrounding community. In accordance with the objectives to be achieved, this research using descriptive qualitative research method. The data was collected by conducting direct observation at the research site by interviewing and distributing questionnaires, and tracking the related documents. The results of this study are expected to provide a comprehensive argument of the phenomenon of PETI in West Dumoga, Bolaang Mongondow District, North Sulawesi Province along with the ecological, economic and social impacts. Furthermore, the results of this study is expected to be a contribution of thought to the Government of Bolaang Mongondow District in policy making and solving problems of PETI. This research is also expected to be a source of reference for related parties and society in general.